UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA MATERI KELIPATAN DAN FAKTOR PERSEKUTUAN MENGGUNAKAN MEDIA PAPAN MUSI (MULTIFUNGSI) KELAS IV SDN SIDOREJO O1 - Haliza Nur Laily Abidah; Raras Setyo Retno; Ninik Marginingsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Mathematics is an abstract subject, making the use of concrete media essential for effective learning. This study aims to enhance students' learning outcomes in mathematics, specifically in the topics of multiples and common factors, through the use of Musi (Multifunctional) board media. The research employed Classroom Action Research (CAR) methodology, utilizing observation techniques and tests with data collected via observation sheets and test questions. The data were analyzed using descriptive statistics. The study involved 21 fourth-grade students from SDN Sidorejo 01. The results showed an improvement in students' learning outcomes from Cycle I to Cycle II. The average score of fourth-grade students increased from 79.76 in Cycle I to 88.33 in Cycle II.